White collar Zen : using Zen principles to overcome obstacles and achieve your career goals - Heine, Steven, 1950- (OUP E-Books., 2005)
It is said that in traditional Japan the samurai embraced Zen because it helped them to be fearless in adversity, to act quickly and decisively, and to keep focused on their ultimate goal. In White Collar Zen, Steven Heine shows how, by applying Zen principles in our working lives, we can achieve the same results for ourselves. Heine describes the way Zen embraces two different yet harmonious paths. The Way of the Hermit teaches detachment--the mental clarity you need to view your situation dispassionately and impartially, to perceive who is an ally and who is a competitor, to understand what.